Multiple endoscopic biopsies in research subjects: safety results from a National Institutes of Health series - Yao, Michael D. (Gastrointest Endosc, 2009)
BACKGROUND: Routine endoscopic mucosal biopsies are generally considered safe. However, the outcomes of performing large numbers of biopsies in subjects enrolled in research protocols have not been reported. OBJECTIVE: Our purpose was to assess the safety of taking numerous mucosal biopsy specimens during endoscopic procedures (eg, >20/endoscopic procedure) in research subjects. DESIGN: Single-center retrospective chart review. SETTING: Research hospital: National Institutes of Health (NIH) Clinical Center. PATIENTS: Volunteers who underwent research protocol endoscopies with large numbers of biopsies during 2001 to 2008 at the NIH. MAIN OUTCOME MEASUREMENTS: Charts were reviewed for the occurrence of procedure-related major/minor complications. RESULTS: A total of 253 research endoscopies were performed on 133 patients: 169 colonoscopies, 64 sigmoidoscopies, and 20 upper endoscopies. A total of 9,661 biopsy specimens were obtained for research and histopathologic examination (mean 38.2 ± 15.6 per procedure). No major complications were identified. Minor complications occurred with 13 (5.1%) lower endoscopic procedures and included self-limited bleeding (4), pain (5), or both (4). There was no statistically significant association between the number of biopsies, type of procedure, location of research biopsies, operator, polypectomy, or the use of nonsteroidal anti-inflammatory drugs and the risk of complications. LIMITATIONS: Retrospective design, modest sample size. CONCLUSIONS: This is the first report on the safety of performing large numbers of endoscopic biopsies in research subjects. This practice is well tolerated and appears to have no more than minimal risk without appreciably increasing the risk of otherwise routine endoscopy.